2006
DOI: 10.1371/journal.pone.0000102
|View full text |Cite
|
Sign up to set email alerts
|

Strong HIV-1-Specific T Cell Responses in HIV-1-Exposed Uninfected Infants and Neonates Revealed after Regulatory T Cell Removal

Abstract: Background In utero transmission of HIV-1 occurs on average in only 3%–15% of HIV-1-exposed neonates born to mothers not on antiretroviral drug therapy. Thus, despite potential exposure, the majority of infants remain uninfected. Weak HIV-1-specific T-cell responses have been detected in children exposed to HIV-1, and potentially contribute to protection against infection. We, and others, have recently shown that the removal of CD4+CD25+ T-regulatory (Treg) cells can reveal strong HIV-1 specific T-cell respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
103
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 53 publications
(52 reference statements)
11
103
0
8
Order By: Relevance
“…Previous studies by our group and others in perinatal HIV-exposed infants have reported evidence of HIV-specific immune response (4,(18)(19)(20)(21)(22)(23)(24)(25). HIV-specific immune response has also been observed in exposed noninfected adults (26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies by our group and others in perinatal HIV-exposed infants have reported evidence of HIV-specific immune response (4,(18)(19)(20)(21)(22)(23)(24)(25). HIV-specific immune response has also been observed in exposed noninfected adults (26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 54%
“…A systematic review of these studies suggests that natural resistance to HIV infection in highly exposed individuals is mediated by multiple mechanisms, conferring on them an ''immunologic advantage'' that may be related to innate and/or adaptive immune systems. 66,67 Although offering only a partial explanation to the natural resistance to HIV infection, 68 observations in female sex workers in Nairobi with frequent HIV exposure, [69][70][71] in exposed uninfected infants with strong HIV-1-specific T cell responses, 72 and more recently in discordant couples 73 suggest that recurrent viral exposure may lead to priming of HIV-specific systemic and mucosal immune responses. These findings suggest that persons receiving PrEP who are exposed to HIV may generate HIV-specific T cell responses, potentially contributing to protection against the establishment of HIV infection.…”
Section: Mucosal Exposure In the Absence Of Chronic Infection Can Indmentioning
confidence: 99%
“…HIV-1 specific immune responses have been reported in children who have been exposed to the virus yet remained uninfected leading to a state of immune activation [6]. CD8+ immune responses to HIV-1 Env, Gag, and Nef proteins have been shown in the peripheral blood of these infants early after birth [7].…”
mentioning
confidence: 99%
“…However, these studies were prior to use of maternal HAART and is likely that these children were exposed to high levels of maternal HIV viremia [7,8]. Even in children exposed perinatally to HAART, HIV-1 specific immune responses even in the setting of low maternal viremia leads to low level of immune activation which is highest in the cord blood and lower in the peripheral blood [6]. This may be either due to infected maternal lymphocytes or activated antigen presenting cells which may have microtransfused across the placenta stimulating the fetal immune system [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation